1992
DOI: 10.1038/bjc.1992.235
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetic advantages of isolated limb perfusion with melphalan for malignant melanoma

Abstract: Summary We describe melphalan pharmacokinetics in 26 patients treated by isolated limb perfusion (ILP). Group A (n = 11) were treated with a bolus of melphalan (1.5 mg kg-'), and in a phase I study the dose was increased to 1.75 mg kg-'. The higher dose was given as a bolus to Group B (n = 9), and by divided dose to Group C (n = 6).Using high performance liquid chromatography (HPLC) the concentrations of melphalan in the arterial and venous perfusate (during ILP) and in the systemic circulation (during and aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Traditionally a perfusion time of 1 h has been adopted for ILPs in patients with melphalan based on pharmacokinetic patterns that request a duration of at least 30 min. The pharmacokinetic profile of melphalan in the perfusate in our model showed a similar rapid decrease in melphalan concentrations as was previously demonstrated by others (Benckhuijsen et al, 1988;Scott et al, 1992). We therefore did not study perfusions longer than 30 min and were more interested if identical results could be obtained after shorter perfusions.…”
Section: Discussionsupporting
confidence: 59%
“…Traditionally a perfusion time of 1 h has been adopted for ILPs in patients with melphalan based on pharmacokinetic patterns that request a duration of at least 30 min. The pharmacokinetic profile of melphalan in the perfusate in our model showed a similar rapid decrease in melphalan concentrations as was previously demonstrated by others (Benckhuijsen et al, 1988;Scott et al, 1992). We therefore did not study perfusions longer than 30 min and were more interested if identical results could be obtained after shorter perfusions.…”
Section: Discussionsupporting
confidence: 59%
“…Flow and melphalan concentration It has been stated that it is desirable to know the proportions of administered melphalan taken up by the tissues and the tumours in a leg during ILP (Scott et al, 1992b). We found that the perfusion flow rate increased proportionally more (1.5-fold) in the skin, fat and muscle than in the tumour (1.2-fold) of the melanoma-bearing rat hindlimb, when the perfusion rate is doubled from 4 to 8 ml min-'.…”
Section: Discussionmentioning
confidence: 99%
“…In the clinical setting, after a 90 min ILP more leakage and other perfusion related problems were seen which was uncomfortable for patient and surgeon. Whereas TNF concentrations remain stable during perfusions, from pharmacokinetic studies of Melphalan it can be derived that there is rapid uptake by the tissues of the limb and almost all uptake of the drug occurs during the first 30 min, so the shortest duration for an effective isolated limb perfusion should be 30 min [33]. With shorter perfusions lesser efficacy was observed, probably due to the fact that exposure times over 20 min are needed to get the vascular occlusive and destructive effects of TNF, needed for adequate tumor responses [13,14].…”
Section: Discussionmentioning
confidence: 99%